1995
DOI: 10.1046/j.1471-4159.1995.65041805.x
|View full text |Cite
|
Sign up to set email alerts
|

Myelin P0 Glycoprotein and a Synthetic Peptide Containing the Palmitoylation Site Are Both Autoacylated

Abstract: P0, the major protein of the PNS myelin, is palmitoylated at the cytoplasmic Cys153. To gain insights into the mechanism of P0 acylation, the in vitro palmitoylation of both P0 and a synthetic Cys153‐containing octapeptide was studied. Incubation of PNS myelin membranes or isolated P0 with [3H]palmitoyl‐CoA resulted in specific labeling of this protein, suggesting that the reaction is nonenzymatic. Incorporation of the labeled fatty acid into P0 was not affected by boiling the isolated P0 for 15 min before inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 22 publications
0
35
0
Order By: Relevance
“…It has been shown that, under certain conditions, the uncatalyzed palmitoylation reaction requires only five times the activation energy than the PAT-catalyzed reaction (40). This could mean that just approaching the two substrates could produce reaction rates that allow the detection of palmitoylated substrates in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that, under certain conditions, the uncatalyzed palmitoylation reaction requires only five times the activation energy than the PAT-catalyzed reaction (40). This could mean that just approaching the two substrates could produce reaction rates that allow the detection of palmitoylated substrates in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Sallustio et al (2000) demonstrated that covalent binding of nafenopin to human liver proteins is directly associated with formation of a nafenopin acyl-CoA thioester intermediate. A number of studies on protein fatty acylation have shown that endogenous acyl-CoAs, including palmitoyl-CoA and arachidonoyl-CoA, can react nonenzymatically with sulfhydryl groups on proteins and peptides in vitro in a time-and concentration-dependent fashion (Bharadwaj and Bizzozero, 1995;Duncan and Gilman, 1996). Our recent studies with 2-phenylpropionic acid (2-PPA 3 ) demonstrated that 2-phenylpropionyl-S-acyl-CoA (2-PPA-CoA) was able to acylate glutathione sulfhydryl to form 2-PPA-S-acyl-glutathione at a rate that was approximately 70-fold more rapid than the similar reactions with 2-PPA-1-O-acyl glucuronides .…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that the free amine of glycine, even under conditions in which the amine is protonated (pH 7.5), was acylated by salicyl-CoA to form salicyluric acid. A number of studies have been conducted to characterize the nonenzymatic acylation of protein sulfhydryls by endogenous acyl-CoA derivatives in vitro (Bharadwaj and Bizzozero, 1995;Yamashita et al, 1995;Duncan and Gilman, 1996). In such experiments, endogenous acyl-CoA derivatives, including palmitoyl-CoA and arachidonoyl-CoA, have been shown to react spontaneously with cysteine-containing proteins and peptides to form thioester conjugates in a time-and concentration-dependent fashion.…”
mentioning
confidence: 99%